PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA KARYAWAN PROMOTOR BRAND REXI ACCESSORIS DI KOTA BENGKULU) - Gunandra, Davin; Meilaty Finthariasari (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2024)
This study aims to determine the effect of leadership style, motivation and work discipline on the performance of Brand Rexi promoter employees in Bengkulu. Respondents of this study were employees of Brand Rexi promoters in Bengkulu totaling 36 employees. The sampling technique used in this study was accidental sampling. Data analysis techniques using multiple linear regression analysis, coefficient of determination and hypothesis testing. Based on the results of research on leadership style, motivation and work discipline simultaneously or together have a significant effect on the performance of employees of the Rexi Brand promoter in Bengkulu City with a probability value (sig) of 0.000 <0.05. As well as the leadership style variable with a probability value (sig) of 0.034 <0.050 has a significant effect on employee performance. Motivation with a probability value (sig) of 0.008 <0.05 has a significant effect on employee performance. And work discipline with a probability value (sig) of 0.000 <0.05 has a significant effect on employee performance.